PEMAKNAAN TERHADAP KONSEP PENYITAAN DAN URGENSI PENYITAAN TERHADAP AKUN MEDIA SOSIAL SEBAGAI BARANG BUKTI TINDAK PIDANA MAYAANTARA (Lex Jurnalica, 2022)
ABSTRACTThe development of information technology causing various new crimes. Therefore, the rules of substantive criminal law are constantly evolving to regulate criminal liability for any criminal actors who commit crimes related to information technology. The development of substantive criminal law must be followed by the development of procedural criminal law. The process of law enforcement against conventional criminal cases is certainly different from law enforcement against cybercrime. This paper will describe the confiscation of social media accounts that are used as a means to commit cybercrimes, such as the spread of hate speech, fake news, electronic information containing insults. The meaning of the word confiscation needs to be reviewed considering that the evidence is not an object in the sense of a tangible object that can be physically transferred.This research is a normative research, using a statutory approach and a conceptual approach. The research was conducted by means of a literature study. The legal materials used are legislation, and legal literature (books, journals).Based on the analysis that has been carried out, it was found that the confiscation of social media accounts is actually an act of law enforcement in limiting the access rights of account owners. It is different from the physical definition of beslag. The confiscation of social media accounts in Indonesia does not yet have clear arrangements regarding the implementation procedures, as well as regarding restrictions on conditions/under what circumstances social media accounts may be subject to confiscation.Keywords: confiscation, social media, evidence